Our family has cancer, too! - Clifford, Christine K., 1954-; Lindstrom, Jack.; ebrary, Inc. (Duluth, MN : Pfeifer-Hamilton Publishers, 1998)
When their mother is diagnosed with cancer, sixth grader Tim and his younger brother visit her in the hospital, learn about radiation and chemotherapy, and help with the chores at home.
Electronic reproduction.
Keywords: Cancer -- Juvenile literature; Tumors -- Juvenile literature; Electronic books